Workshop Implementasi Kurikulum Merdeka: Peran Komite Sekolah - Meiliza, Zuhra; Muhammad, Fadhil; Fandini, Intan; A. A, Nurfadillah; Herawati, Cici (Lembaga Dongan Dosen, 2024)
Workshop on the implementation of the independent curriculum: the role of the school committee was an activity that is carried out with the aim of providing understanding to teachers about the role of the school committee in the process of school management. The activity will be held from May 15 – June 24, 2024. The location of this activity was SD Negeri No. 10 Galung, Majene. Participants in the activity amounted to 8 teachers. The team involved in the implementation of the activity was 2 lecturers and involved 2 PGSD students. The implementation of activities uses several stages including team formation, observation, committee meetings, implementation of activities and evaluation of activities. Based on the results of the evaluation before the activity, it was obtained that only one teacher answered that the participation of parents and the community in their role in the school committee had been carried out in accordance with the law. Meanwhile, the evaluation of the implementation of the activity, namely the implementation of the activity, showed the results of 87.5 categories very good and the participants' understanding of the role of the school committee after this workshop activity showed 75 categories of very good and 25 categories of good.